Evaluation of Ofloxacin in the Treatment of Laparoscopically Documented Acute Pelvic Inflammatory Disease (Salpingitis) - J. F. Peipert; R. L. Sweet; C. K. Walker; J. Kahn; K. Rielly-Gauvin (Hindawi Limited, 1999)
Objective: To evaluate the safety and efficacy of intravenous and oral ofloxacin monotherapy in the treatment of laparoscopically documented acute pelvic inflammatory disease (PID).